A History of Wine in Europe, 19th to 20th Centuries, Volume II Markets, Trade and Regulation of Quality - Conca Messina, Silvia A.; Le Bras, Stéphane; Tedeschi, Paolo; Vaquero Piñeiro, Manuel (Palgrave Studies in Economic History, 2019)
X, 277 p. 18 illus., 17 illus. in color.